Prevalence of Turkish Ministry of Health e-Nabız application usage and the factors affecting its use - ÖZAYDIN, AYŞE NİLÜFER (My University, 2024)
Objective: In this study, the frequency of using the e-Nabız application and the factors affecting its use were studied among adults living in a district of northern Turkey. Materials and Methods: In this cross-sectional study, the sample (n:555, N:9264) was selected from those who applied, for any reason, to the only hospital in the district between March 1 and December 31, 2020. Data were collected by an online questionnaire (10 February–29 March 2021). Ethical permissions were obtained from the Ministry of Health, Republic of Turkey and the Marmara University, School of Medicine Clinical Researches Ethics Committee (05.02.2021/09.2021.70). All the participants gave informed consent. Results: Among 458 participants, the response rate was 82.5% and 59.4% of the respondents were female. The median age was 44.0 years (44.7±13.7; range: 19–72). 57.4% of the females and 69.4% of the males had registered for the application (p: 0.006), and 56.6% of the females and 68.8% of the males had used e-Nabız (p: 0.011). The males, aged 26–45, with high school and above education levels, working in the public sector with a good monthly income, were the group with the highest usage of e-Nabız (respectively p: 0.001, p: 0.001, p: 0.001, and p: 0.001). Current health status did not affect the usage of e-Nabız (p:0.144). Conclusion: We can promote environmentally friendly usage by enhancing health literacy through e-Nabız and securely storing personal health records. Therefore, educational sessions can be organized to inform citizens about the services provided by e-Nabız. Keywords: Digital health applications, e-Health applications, Electronic medical records, Health information technologies
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Digital health applications; e-Health applications; Electronic medical records; Health information technologies